Deconstructing Qawwām: Derrida's Philosophical Hermeneutics and the Reconfiguration of the Role of Gender in Islamic Thought - Rezwandi Rezwandi; Ilhammuddin Arrasyid Matondang; Nur Annisa Fitria (Aqlania, 2025)
The issue of gender is a never-ending issue, especially related to the balance of gender roles in the reality of everyday life. The focus of this study is to analyze the balance of gender roles in the QS review. al-Nisā (4): 34 about Qawwām by involving a theory from a famous figure, namely Jacques Derrida's deconstruction theory. The data collection method used is qualitative, which typically requires analysis. Then the results of the discussion in this study are: First, that by using Derrida's deconstruction, it can provide color in a person's thinking style when understanding a text, the text will not be interpreted with only one meaning or even a final meaning, but will continue to produce new meanings that continue to be sustainable. Second, deconstruction does not justify or blame, but serves as a mediator by examining the meanings that emerge from reading the conditions of social reality. Third, Derrida's deconstruction can reveal that the term Qawwām does not immediately refer to male superiority, but rather to a situational division of roles. Thus, the relationship between husband and wife can be seen as a dynamic partnership that complements rather than hierarchizes.